NGX6 inhibits cell invasion and adhesion through suppression of Wnt/β-catenin signal pathway in colon cancer - Guo, Qin (Oxford University Press, 2010)
Colon cancer is a common malignant tumor that is associated with increased morbidity and mortality. Nasopharyngeal carcinoma-associated gene 6 (NGX6) is a novel candidate suppressor gene of tumor metastasis, which is down-regulated in colon cancer. This study was designed to investigate the roles of NGX6 on the growth and invasiveness of human colon cancer cell line, HT-29, and to elucidate the molecular mechanism of their action. Results showed that NGX6 could inhibit the invasiveness and extracellular matrix adhesion of HT-29 cells and restore the gap junctional intercellular communication of cells. Moreover, NGX6 could suppress the translocation of β-catenin from nucleus and cytoplasm to plasma membrane, inhibit the activity of TCF4 transcript factor, and down-regulate the expression of Wnt-direct-targeted genes c-myc, cyclin D1 and COX-2. We suggested that NGX6 inhibits cell invasion and adhesion through the suppression of Wnt signal pathway in colon cancer.